Asian Perspective of Population 2019: A Sociological Appraisal - Mohammad Taghi Sheykhi (Budapest International Research and Critics University, 2020)
The present attempt fulfills the urgent need of researchers in the valuable field of sociology, economics and statistics. The author has gathered the material from various sources of population data. As data on fertility, mortality and migration are ever changing, sociologists and demographers need to compare and analyze population change and structure every now and then, to introduce and build up new strategies leading to favorable population status. In this way, remedies and reforms could be reached wherever possible. In order to enable the readers to have a comparative image of growth of population in Asia, an abridged table has been provided. Such a comparative study is necessary to understand population problems in Asia with about 60% of world population. Factors affecting population distribution are know as geographic, social, economic and demographic. One of the most important aspects of population study in modern time is the tempo of urbanization which is the result of population growth.